A América do Sul na cartografia renascentista - Maria Márcia Magela Machado; Úrsula Ruchkys (Navigator)
From the 1550’s Antwerp became the main center of production and also print world maps and atlases. In these maps, the New World began to take shape. However, the mathematization of representation of space that characterized the Renaissance cartography did not prevent that large distortions were imputed to the territories of the colonies overseas. The lack of knowledge of the geographical reality and imagination, fueled by stories about these territories, were sometimes responsible for the deformations. This cartography recorded glare caused by the enormous treasures found by the Spaniards in Peru. In several maps published in the Renaissance, the Peruvian territory appears enlarged, occupied almost the entire central area of South America to the detriment, mainly, of Brazilian territory, that greatly underestimated, comes to seem a peninsula. A current look of the deformed images of South America in these maps leads us to an anamorphic. It is as if the territories of Brazil and Peru have undergone a transformation space in which the gradient of Euclidean distance was converted into a new metric: the treasures so far discovered.